Multisystem inflammatory syndrome in children. An emerging clinical challenge for pediatric surgeons in the COVID 19 era - Francesco Valitutti; Alessandra Verde; Angela Pepe; Eduardo Sorrentino; Deborah Veneruso; Giusy Ranucci; Francesca Orlando; Augusto Mastrominico; Mia Giovanna Grella; Claudia Mandato (Elsevier, 2021)
Background/purpose: Multisystem inflammatory syndrome in children (MIS-C) is a potentially life-threatening condition occurring 2-6 weeks after Coronavirus disease 2019 (COVID-19) in previously healthy children and adolescents, characterized by clinical and laboratory evidence of multiorgan inflammation. We reported the case of a 6-year-old child presented with acute abdomen and then diagnosed with MIS-C. In addition, to better portray this new entity, we performed a systematic review of MIS-C gastrointestinal features and particularly on those mimicking surgical emergencies. Methods: We described the clinical presentation, the diagnostic approach and the therapeutic outcomes of our MIS-C patient. Parallel to this, we conducted a systematic literature search using Google Scholar, PubMed, EMBASE, Scopus, focusing on gastrointestinal MIS-C. Results: Our patient was initially assessed by the surgical team due to his query acute abdomen. Following the diagnosis of MIS-C with myocarditis, intravenous methylprednisolone (2 mg/Kg/day) and intravenous immunoglobulins (2 gr/Kg single infusion) were promptly started, leading to clinical improvement. According to our literature search, patients with MIS-C have a high rate of severe abdominal symptoms resembling surgical emergencies (appendicitis, obstruction, etc.) and a not negligible number of those patients have been surgically explored with variable findings. Conclusions: We encourage pediatric surgeons in the upcoming months of COVID-19 pandemic to evaluate myocardial function prior to surgical abdominal exploration. In children with query acute abdomen, MIS-C should be promptly ruled out in order to avoid unnecessary surgeries that could worsen the already frail outcome of this new syndrome. Nevertheless, it should be considered that MIS-C might well encompass complications (e.g. appendicitis, segmental intestinal ischemia) which need swift surgical treatment.